2015
DOI: 10.5392/jkca.2015.15.10.504
|View full text |Cite
|
Sign up to set email alerts
|

Financial Aspects of Korean Chaebol Firms in terms of Trend of Cash Holdings and Type of a Domestic Bourse

Abstract: This study addresses one of the curent issues in modern finance, which investigates financial profile on the levels of the chaebol firms' cash hoardings in the domestic capital market. Iit may be imperative to search for robust and consistent financial determinants of cash holdings as well as identifying any changes or trend of the determinants affecting the corporate cash reserves in the post-era of the global financial turmoil, considering that interest parties at the government and corporate levels, still s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Another prominent factor affecting corporate cash retention rate was identified as AGENCY1 which showed its negative linkage to the level of cash holdings. This was consistent with the outcome obtained from [11] and [13].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Another prominent factor affecting corporate cash retention rate was identified as AGENCY1 which showed its negative linkage to the level of cash holdings. This was consistent with the outcome obtained from [11] and [13].…”
Section: Discussionsupporting
confidence: 81%
“…Among the total number of twelve explanatory variables which had also been employed in the preceding study of [11], four or five predictors showed their statistically discriminating power at the …”
Section: Table 3 Results Of the Estimated Coefficient Of The Idvs Onmentioning
confidence: 99%